A Teacher in the Era of the Spread of Artificial Intelligence Applications – Challenges and Difficulties - ŚCIERANKA, SANDRA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
The tasks of a modern teacher are definitely different from those they had to perform a decade ago. In the era of various changes taking place, constantly developing, but also accompanying digitization in every sphere of life, the role of the teacher takes on a new meaning – flexibility and openness to changes on their part become necessary. Therefore, teachers face new challenges, roles and skills to expand. The conducted considerations are aimed at showing the impact of digitization both on the daily work of the teacher, the performance of professional functions, as well as his relationship with students. The punchline becomes the need to use artificial intelligence tools, as well as the essence and necessity of media literacy of modern teachers, which is reflected in the entire didactic process carried out among students shaped by digitization and the world of media. Among the others, the aim of the work was to determine attitudes of the educators (on the rating scale) about the presented approach to the work.